2017
DOI: 10.1007/s00253-017-8429-8
|View full text |Cite
|
Sign up to set email alerts
|

Phage-host associations in a full-scale activated sludge plant during sludge bulking

Abstract: Sludge bulking, a notorious microbial issue in activated sludge plants, is always accompanied by dramatic changes in the bacterial community. Despite large numbers of phages in sludge systems, their responses to sludge bulking and phage-host associations during bulking are unknown. In this study, high-throughput sequencing of viral metagenomes and bacterial 16S rRNA genes were employed to characterize viral and bacterial communities in a sludge plant under different sludge conditions (sludge volume index (SVI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…These results are in accordance with the known prokaryote diversity that dwells in each of these ecosystems. 8,[16][17][18][19][20][21][22] Although this agreement between virus and host community composition is to be expected, it is seldom observed in studies of viral ecology based on metagenomics because classical methods leave the majority of viruses without host predictions. RaFAH circumvents these issues by providing an accurate and complete description of viral communities regarding their targeted hosts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with the known prokaryote diversity that dwells in each of these ecosystems. 8,[16][17][18][19][20][21][22] Although this agreement between virus and host community composition is to be expected, it is seldom observed in studies of viral ecology based on metagenomics because classical methods leave the majority of viruses without host predictions. RaFAH circumvents these issues by providing an accurate and complete description of viral communities regarding their targeted hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Test Set 3 comprised a collection of 61,647 viral genomic sequences from studies that spanned multiple samples from permafrost, 8 ⁠ marine, 49 ⁠ human gut, 50 ⁠ freshwater⁠, 19 soil⁠, 51 hypersaline lakes, 52 ⁠ hydrothermal springs (Fredrickson et al., unpublished data obtained from IMG/VR⁠), 53 and sludge bioreactor 18 ⁠ habitats. These sequences were assigned to putative hosts through the classical host-prediction pipeline described above for the GLUVAB genomes and also using RaFAH.…”
Section: Methodsmentioning
confidence: 99%
“…With the advent of next-generation DNA sequencing (NGS) of isolated phages and metagenomics studies, this situation has improved [95,96,97,98,99,100,101,102,103,104,105,106]. It is now clear that the genomes of many bacteria present in activated sludge systems contain CRISPR-Cas regions, suggesting that these have in the past been infected by phage, and therefore their presence makes the problem of determining host/phage relationships in the absence of conventional ability to culture host cells, and consequently phage recovery [107].…”
Section: Bacteriophages In Artificial Environmentsmentioning
confidence: 99%
“…Phages have also been held responsible for deterioration of the phosphorous removal capacity. Thus, it has been suggested that exposure of Accumulibacter to several stress factors induced the lytic cycle in prophages, known to occur in Accumulibacter genomes [107,109,110]. This led to an increase in VLP numbers, a decrease in the cell numbers of Accumulibacter , i.e., a phosphorous accumulating organism, and in the copy numbers of ppk1 , the gene responsible for the synthesis of polyphosphate.…”
Section: Bacteriophages In Artificial Environmentsmentioning
confidence: 99%
“…Bacterial viruses (also bacteriophages or phages) are present in large number and are widely distributed in naturally functioning microbial ecosystems, including engineered environments, where they have a recognized key role in controlling microbial abundance and composition [13]. Well-designed experiments examining single host-phage pairs in the laboratory have advanced significantly our understanding of phenotypic and genetic diversification in bacteria and phages [46].…”
Section: Introductionmentioning
confidence: 99%